Inside Cover: Efficient Self‐Assembly of Di‐, Tri‐, Tetra‐, and Hexavalent Hosts with Predefined Geometries for the Investigation of Multivalency (Chem. Eur. J. 37/2015). Issue 37 (7th September 2015) - Linder, Igor; Leisering, Stefan; Puttreddy, Rakesh; Rades, Nadine; Rissanen, Kari; Schalley, Christoph A.
<x xml:space="preserve">Abstract</x> A multivalency happy hour for a series of di‐ to hexavalent hosts with predefined geometry and number of binding sites that were self‐assembled by a coordination‐chemistry approach simply by mixing and stirring (not shaking) convergently synthesized ligands with transition‐metal salts of choice. For more details, see the Full Paper by C. A. Schalley et al. on page 13035 ff.